Archaeological spatial analysis a methodological guide - Gillings, Mark; Hacigüzeller, Piraye; Lock, G. R. |q (Gary R.) (New York Routledge, 2020)
Effective spatial analysis is an essential element of archaeological research; this book is a unique guide to choosing the appropriate technique, applying it correctly and understanding its implications both theoretically and practically. Focusing upon the key techniques used in archaeological spatial analysis, this book provides the authoritative, yet accessible, methodological guide to the subject which has thus far been missing from the corpus. It can be consulted by undergraduate and post-graduate level students as well as instructors, researchers and professionals in archaeology. Each chapter tackles a specific technique or application area and follows a clear and coherent structure. First, is a richly referenced introduction to the particular technique, followed by a detailed description of the methodology, then an archaeological case-study to illustrate the application of the technique, and conclusions that point to the implications and potential of the technique within archaeology. The book is designed to function as the main textbook for archaeological spatial analysis courses at undergraduate and post-graduate level, while its user friendly structure makes it also suitable for self-learning by archaeology students as well as researchers and professionals"--
Includes bibliographical references and index.
Keywords: patial analysis (Statistics) in archaeology